Information Communication and Technology Skills: A Veritable Tool for Principals' Administrative Effectiveness in Osun State Secondary Schools, Nigeria - Busuyi Francis Olowo; Adedapo Adelokun; Bolanle Oluwatoyin Akinola; Tayo Sikiru Subair (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2021)
The use of Information Communication and Technology (ICT) skills are indispensable and cannot be overemphasized in discharging principals' administrative functions. This paper investigated the use of ICT skills on principals' administrative effectiveness in Osun State secondary schools. The study adopted quantitative approach with a correlational research design. The population comprised all 7,767 teachers in Osun State primary schools. Sample of 385 teachers was randomly selected. An instrument was used to collect data. Data were analysed descriptively and inferentially. The findings indicated that principals in Osun State secondary were highly effective in discharging administrative functions and exhibited moderate use of ICT skills. The study further showed that irregular supply of electricity and lack of fund were factors discovered hindering the principals to use the ICT skills. The study further indicated that there was significant relationship between the between the use of ICT skills and principals' administrative effectiveness. The study concluded that that the principals' use of ICT skills had positive contribution to their administrative effectiveness in Osun State secondary schools. The study implicates that the principals in Osun State and Nigeria at large should acquire and utilize the ICT skills in their administrative functions which would enable them to compete world-widely.